Knowledge about sexually transmitted infections in adolescents from the Naiguatá Parish. La Guaira. Venezuela, 2021 - Bárbara Teresa Zabala Enrique; Natasha Sànchez Bouza; Lourdes Elena Duany Badell; Magdalena Omayda Albelo; Josè Demiàn Rodrìguez Medina; Yusimì Cabada Martìnez (Medisur, 2023)
Foundation: sexually transmitted infections are a problem that can harm human beings, especially adolescents. Objective: to describe the adolescents’ knowledge about sexually transmitted infections from the Naiguatá Parish. La Guaira. Methods: descriptive, cross-sectional study carried out from June to December 2021. The universe of 471 adolescents and a sample of 142 (30.0%) was selected, using the simple random method. A structured survey of eight questions was applied. The analyzed variables were: age, sex, beginning of sexual relations, knowledge about sexually transmitted infections: diseases considered to be sexually transmitted, routes of transmission, clinical manifestations, risk of acquiring them, measures to prevent them, and their complications. Results: the prevailing age was 16 years old and the female sex; 41.5% started sexual relations at 14 years of age. Ignorance of sexually transmitted infections, their transmission routes and their clinical manifestations prevailed. AIDS, syphilis and gonorrhea were identified as sexually transmitted infections; recognized the use of condoms as a form of prevention and death (66.9%) and pelvic inflammation (53.5%) as the main complications of these diseases. Conclusions: the adolescents’ knowledge about sexually transmitted infections continues to be insufficient.